2019
DOI: 10.11591/eei.v8i3.1346
|View full text |Cite
|
Sign up to set email alerts
|

Moving object detection via TV-L1 optical flow in fall-down videos

Abstract: There is a growing demand for surveillance systems that can detect fall-down events because of the increased number of surveillance cameras being installed in many public indoor and outdoor locations. Fall-down event detection has been vigorously and extensively researched for safety purposes, particularly to monitor elderly peoples, patients, and toddlers. This computer vision detector has become more affordable with the development of high-speed computer networks and low-cost video cameras. This paper propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The goal of this subsection is to make a final decision on locating the exact fall frame using previous fall event classification features. Let i represents the current frame, ∆y best ∈ R 1 is calculated based on Equation (8), where y i is the current and y i−1 is the previous output scores in a video sequence of V length. ∆y i is measured since the output scores of fall event classification is in d classes, in which the fall frame is detected when the change in output scores is the biggest.…”
Section: Fall Event Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of this subsection is to make a final decision on locating the exact fall frame using previous fall event classification features. Let i represents the current frame, ∆y best ∈ R 1 is calculated based on Equation (8), where y i is the current and y i−1 is the previous output scores in a video sequence of V length. ∆y i is measured since the output scores of fall event classification is in d classes, in which the fall frame is detected when the change in output scores is the biggest.…”
Section: Fall Event Decision-makingmentioning
confidence: 99%
“…Lastly, the recovery phase is the condition when the person gets up again after the post-fall phase, where the timing is regarded as the response time, T 2 . In general, the main cause for the occurrence of a fall event can be attributed to a loss of balance due to sudden trip or slip, or instability during movements [7,8]. Furthermore, WHO has also reported that the fall event is the second biggest death contributor globally with an estimate of 646,000 cases each year.…”
Section: Introductionmentioning
confidence: 99%
“…1 shows the spatial distribution of the solution set of the optical flow equation. For those images where there are more prominent points, more obvious edge lines, and other information, median filtering is not good, because the filtered image will lose a lot of detailed information [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%